2018
DOI: 10.5867/medwave.2018.02.7187
|View full text |Cite
|
Sign up to set email alerts
|

Are diuretics effective for Ménière`s disease?

Abstract: We identified three systematic reviews including nineteen studies overall, of which four were randomized trials. We concluded it is not clear whether diuretics lead to a symptomatic improvement of vertigo or an objective decrease in hearing loss in patients with Ménière`s disease, because the certainty of the evidence is very low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
3
0
3
Order By: Relevance
“…Diuretics have also been recommended to control vertigo attacks in MD, due to their effects in reducing the endolymphatic pressure and volume. As for steroids and gentamicin, there are no high-quality data demonstrating the efficacy of oral diuretic therapy 30 ; in addition, a meta-analysis from Rosenbaum and Winter 31 concluded that it is not clear if diuretic lead to a symptomatic improvement of vertigo.…”
Section: Discussionmentioning
confidence: 99%
“…Diuretics have also been recommended to control vertigo attacks in MD, due to their effects in reducing the endolymphatic pressure and volume. As for steroids and gentamicin, there are no high-quality data demonstrating the efficacy of oral diuretic therapy 30 ; in addition, a meta-analysis from Rosenbaum and Winter 31 concluded that it is not clear if diuretic lead to a symptomatic improvement of vertigo.…”
Section: Discussionmentioning
confidence: 99%
“…Rosenbaum, however, discussed the potential that a sudden drop in blood pressure caused by diuretics could result in a negative sympathetic response and provide the cochlear vasopressin receptors false information. This would eventually result in permanent inner ear damage (Rosenbaum and Winter, 2018;Crowson et al, 2016).…”
Section: Diureticsmentioning
confidence: 99%
“…En términos farmacológicos, los diuréticos representan el tratamiento de primera elección para disminuir el volumen y la presión endolinfática 13 .…”
Section: Primer Escalónunclassified